Enhancing the impact strength of acrylic resin base plate by adding non-dental E-glass fiber - Mara Gustina; Widjijono Widjijono; Endang Wahyuningtyas (Majalah Kedokteran Gigi Indonesia, 2020)
Non-dental glass fiber is one of the materials that can be used to increase the impact strength of a acrylic resin base plate, containing a similar composition to that of dental e-glass fiber. Orientation and positions of fiber affect the reinforcement effectiveness. This research aimed to examine the effect of the orientation of non-dental glass fiber in the compression position on the impact strength of an acrylic resin base plate. The research was conducted on 16 acrylic resin plates with fiber (65 mm x 10 mm x 2.5 mm) addition. The samples were divided into 4 groups (combination of different woven orientation unidirectional, bidirectional woven in the compression position, and control). The material used in this study was heat-cured acrylic resin QC-20 brand, non-dental glass fiber (without any brand). Impact strength was tested using an impact testing machine. The data obtained were analyzed using one-way ANOVA test and LSD (p<0.05). In this research the impact strength of the base plate with the addition of fiber increased 8.54 ± 2.21; 13.21 ± 2.34; 16.81 ± 2.80 kJ/m2 compared to that of the control group, i.e. 4.98 ± 1.05 kJ/m2. One-way ANOVA test showed a significant effect (p<0.05) of the fiber orientation variations on the compression position. This research concluded that the addition of nondental e-glass fiber (composed of SiO252.56-56.88%), diameter 17.12–20.03 µm) in the compression zone increases theimpact strength of acrylic resin base plate. Fibers with unidirectional orientationprovides the highest increase in the impact strength of acrylic resin base plate.